PENINGKATKAN HASIL BELAJAR PRODUKTIF BOGA MELALUI METODE DEMONSTRASI PADA SISWA KELAS X¬-2 JURUSAN TATA BOGA DI SMK NEGERI 10 MEDAN - Nurpida Marlinang Limbong (MES: Journal of Mathematics Education and Science, 2020)
The purpose of this study was to improve student learning outcomes in Productive Catering learning and to encourage and train Productive Catering teachers at SMK Negeri 10 Medan. Through the demonstration method, it is hoped that it can solve the problems faced by teachers in the classroom related to student learning outcomes by using a systematic way of thinking. To achieve this goal, the researchers collaborated with Productive Catering teachers by conducting classroom action research. This research was conducted in class X-2, Catering Department at SMK Negeri 10 Medan. The classroom action research steps begin with initial dialogue, planning learning actions, implementing actions, observing, reflecting and evaluating. The research was conducted in three cycles, each cycle consisting of two meetings. The results showed that there was an increase in student learning outcomes which means in learning Productive Catering. At the beginning of the research, the students who completed the study were 25% after the research in the first cycle, the students' learning completeness was 31.25% and 50%. In Cycle II, the students' learning completeness was 56.25% and 62.5%, and in the third cycle, the percentage of student learning completeness had met the criteria of 81.25% and 84.375%.